2018
DOI: 10.1080/14397595.2018.1480915
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intravenous belimumab in Japanese patients with systemic lupus erythematosus: A subgroup analysis of a phase 3 randomized placebo-controlled trial

Abstract: In Japanese patients with SLE, belimumab improved disease activity, with efficacy and safety results similar and consistent to the pivotal Phase 3 trials, suggesting that belimumab is a potential treatment option in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…A total of 70 unique publications (3,4,10,11, comprised of 27 clinical studies, 16 epidemiologic studies, and 27 studies reporting economic and humanistic burden and unmet need met the inclusion criteria (see Supplementary Appendix C, available at http:// onlinelibrary.wiley.com/doi/10.1002/acr.24431/abstract). Most of the studies were conducted in China (n = 14) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), and Taiwan (n = 12) (20,22,24,25,45,52,56,60-62, 64,69), followed by Korea (n = 9) (17,26,32,42,44,53,63,72,76), Australia (n = 7) (4,18,39,49,50,57,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 70 unique publications (3,4,10,11, comprised of 27 clinical studies, 16 epidemiologic studies, and 27 studies reporting economic and humanistic burden and unmet need met the inclusion criteria (see Supplementary Appendix C, available at http:// onlinelibrary.wiley.com/doi/10.1002/acr.24431/abstract). Most of the studies were conducted in China (n = 14) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), and Taiwan (n = 12) (20,22,24,25,45,52,56,60-62, 64,69), followed by Korea (n = 9) (17,26,32,42,44,53,63,72,76), Australia (n = 7) (4,18,39,49,50,57,…”
Section: Resultsmentioning
confidence: 99%
“…Disease characteristics of patients in included studies. Disease characteristics were reported for SLE patients in studies from Australia (n = 6) (4,18,39,50,57,66), China (n = 15) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Hong Kong (n = 6) (10,30,46,71,80,81), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), Korea (n = 7) (17,26,41,42,44,63,72), Singapore (n = 4) (27,48,55,70), and Taiwan (n = 10) (20,22,24,25,45,52,…”
Section: Significance and Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the drug inhibits the proliferation of connective tissue, controls the permeability of cell membranes, and reduces severe exudation, thereby suppressing the immune response and reducing the inflammatory response. However, it has been clinically found that the therapeutic effect of prednisone when used as a single drug, is poor, while the addition of immunosuppressive therapy effectively improves clinical efficacy [14,15]. Cyclophosphamide, a clinically potent immunosuppressant, acts as an antiinflammatory agent by effectively blocking the release of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…These studies consistently showed significant improvement in disease activity with belimumab versus placebo [14][15][16][17]. A subgroup analysis of the North-East Asia study, conducted to specifically assess the safety and efficacy of belimumab within the Japanese population, also demonstrated improved disease activity, as assessed by the SLE Responder Index (SRI) 4 at Week 52 [18].…”
Section: Introductionmentioning
confidence: 91%